Callorhinus ursinus - Jo, Yeong-Seok; Baccus, John T.; Koprowski, John L. (Zenodo, 2018)
Callorhinus ursinus (Linnaeus, 1758) —Northern Fur Seal Phoca ursina Linnaeus, 1758 p.37; Type locality- Bering Island. Callorhinus curilensis Jordan and Clark in Jordan et al. , 1899 p.3; Type locality- Kuriles. Otoes ursinus : Kuroda, 1938 p.22. C. ursinus : Ellerman & Morrison-Scott, 1951 p.322; Won, 1958 p.436; Won, 1967 p.94; Won, 1968 p.331; Won & Smith, 1999 p.29; Kim 2004 p.190. C . ursinus curilensis : Ellerman & Morrison-Scott, 1951 p.322. Range: The long migratory route for C . ursinus courses mostly along the eastern coast and sometimes the southern shore of the Korean Peninsula (Fig. 60). This species frequently occurs on Dok-Island. Often, fishermen incidentally catch northern fur seals in the East Sea during winter. Remarks: Marine biologists have long recognized the monotypy of Callorhinus ursinus . Mitochondrial DNA and microsatellite data identified a weak population structure across the extensive range of this taxon (Dickerson et al . 2010). Conservation status: North Korea made C. ursinus and their habitat in Uam Ri, Hamgyeongbuk Province a Natural Monument. The Ministry of Environment of South Korea designated C . ursinus as an Endangered Species in 1997. Also, the Ministry of Land, Transports and Maritime Affairs named the northern fur seal a protected marine species in 2007. Published as part of Jo, Yeong-Seok, Baccus, John T. & Koprowski, John L., 2018, Mammals of Korea: a review of their taxonomy, distribution and conservation status, pp. 1-216 in Zootaxa 4522 (1) on pages 92-93, DOI:10.11646/zootaxa.4522.1.1, http://zenodo.org/record/2610198